"We’re led by stupid people": exploring Trump’s use of denigrating and deprecating speech to promote hatred and violence - Valcore, Jace (Crime, law and social change, 2023)
In response to a call for criminologists to consider the impact of former President Donald Trump’s presumed criminality, we analyze verbal-textual hostility (VTH) in Trump’s campaign speeches. Politicians have particular power and reach with their speech and their use of VTH is an important part of the trifecta of violence. Using a framework informed by linguistic theory and previous analysis of hate speech in recorded hate crimes, we present the categories of deprecation and denigration, and discuss their relationship to domination. In context, these forms of VTH enhance and serve as precursors to more violent speech and acts.